Education as Performative Contradiction: Limits (And Possibilities) of Subjectification in the Anthropocene - Audrius Pocius (Acta Paedagogica Vilnensia)
An environmentally reoriented educational policy is oftentimes regarded as the premier locus for a societal response to the climate crisis. As observed by Gough (2021), a general belief shared among both policy makers and academics is a consensus that education needs to be perceived less as an instrument for securing sociocultural reproduction and transmission of existing knowledge and more as a catalyst for social and cultural change. The aim of this article is a critical investigation into possibilities and obstacles for education to achieve such change, given the condition of ‘ontological insecurity’ (Hamilton, 2017) that the Anthropocene implies. It is divided into three parts: 1) following Chakrabarty, I identify the politico-aesthetic challenges posed by anthropogenic climate change and formulate their relevance as an educational ordeal; 2) I enquire about the challenges and possibilities for environmental education to foster societal change and conclude that, while a general policy change toward sustainable education may be insufficient, education remains a premier site where negotiations could take place between the deep-seated beliefs about subjectivity and an open anticipation of unforeseen modes of agency; 3) after providing a comparative analysis of classical humanist Bildung and post-humanist accounts of subjectification in education, I conclude that these approaches constitute a performative contradiction, which allows the experiential challenges of the Anthropocene to be approached in terms of a reimagined aesthetic education thematized as a critique of (human) capacity.